2006
DOI: 10.1016/j.ijantimicag.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of MDL 28170, a potent calpain inhibitor

Abstract: Several calpain inhibitors are under development and some are useful agents against important human pathogens. We therefore investigated the effect of MDL 28170, a potent calpain inhibitor, on the growth of Leishmania amazonensis. After 48 h of treatment, the inhibitor exhibited a dose-dependent antileishmanial activity, with a 50% lethal dose (LD(50)) of 23.3 microM. The inhibitor promoted cellular alterations, such as the parasites becoming short and round. A calpain-like protein migrating at 80 kDa was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Our results showed that this calpain inhibitor promoted cellular alterations and arrested the growth of the proliferative forms of both parasites in a dose-dependent manner [7], [14]. Previous works from our group also showed that MDL28170 acted against all the morphological stages found in T. cruzi , without displaying any relevant cytotoxic effect on mammalian host cells [14], [15].…”
Section: Introductionsupporting
confidence: 69%
“…Our results showed that this calpain inhibitor promoted cellular alterations and arrested the growth of the proliferative forms of both parasites in a dose-dependent manner [7], [14]. Previous works from our group also showed that MDL28170 acted against all the morphological stages found in T. cruzi , without displaying any relevant cytotoxic effect on mammalian host cells [14], [15].…”
Section: Introductionsupporting
confidence: 69%
“…The effects of pepstatin A (Sigma Chemical Co., USA) on epimastigotes of T. cruzi were assessed by a method similar to that previously described elsewhere (d' Avila-Levy et al 2006). Briefly, epimastigotes were counted using a Neubauer chamber and resuspended in fresh BHI+FBS medium to a final concentration of 5×10 6 viable epimastigotes per milliliter.…”
Section: Effects Of Pepstatin a On The Growth Rate And Cell Morphologymentioning
confidence: 99%
“…In L. major, it was demonstrated that a calpain related protein (LmCALP20.2) is up regulated in the promastigote insect stage and LmCALP20.1, coded by the adjacent gene, is up regulated in the subsequent metacyclic insect stage [149]. Our group demonstrated that MDL28170, a potent calpain inhibitor, is capable of reducing promastigote growth in culture and induces cell death [150], probable through apoptosis (unpublished data). A proteomics screen implicated a calpain-related protein in drug resistance in L. donovani clinical field isolates, probably by modulating drug-induced apoptosis [151].…”
Section: Cysteine Peptidasesmentioning
confidence: 83%